Comparison between the diagnostic performance of vessel fractional flow reserve and nonhyperemic pressure ratio for functionally significant coronary stenosis severity as assessed by fractional flow reserve. Issue 1 (8th December 2022) - Ikeda, Kazumasa; Kobayashi, Masatake; Chikamori, Taishiro; Yanaka, Yohei; Takagi, Ryu; Kani, Junya; Oshima, Outaro; Yamada, Satoshi; Hokama, Yohei; Tanaka, Nobuhiro
Abstract: Background: Fractional flow reserve (FFR) and nonhyperemic pressure ratios (NHPRs) have been widely used to assess the functional severity of coronary stenosis. However, their measurement requires using a pressure wire, making their use in all patients difficult. The recently developed vessel fractional flow reserve (vFFR), derived from three‐dimensional quantitative coronary angiography, is expected to serve as a surrogate for pressure wire assessment. Methods: This retrospective study was conducted on patients with intermediate coronary stenosis who underwent FFR and NHPR measurements. The vFFR and NHPR values were compared for diagnosing coronary stenosis as defined by an FFR of ≤0.80, and the number of patients not requiring wire‐based assessment was estimated. Results: In a total of 90 lesions from 74 patients (median [SD] age 75 [12] years; men 80%), the median FFR was 0.78 (0.72–0.84), and 57% of these lesions ( N = 51) exhibited an FFR of ≤0.80. vFFR provided high discrimination for coronary stenosis (area under the curve 0.80, 95% confidence interval 0.70–0.90), which was comparable to that of NHPRs ( p = 0.42). High diagnostic accuracy was consistently observed across a variety of clinical presentations (i.e., old age, diabetes, target coronary artery, and left ventricular hypertrophy) ( p interaction > 0.05). In total, 55 lesions (61%) demonstrated positive or negative likelihood of coronary stenosis when vFFR was <0.73 (specificity 90%) or >0.87 (sensitivity 88%), respectively. Conclusion: vFFR demonstrated excellent diagnostic performance for detecting functionally significant coronary stenosis as evaluated by FFR. vFFR may be used as a surrogate for pressure wire assessment.